Evaluation of a Self-organized Traffic Light Policy - Borm, Michelle; Patch, Brendan; Taimre, Thomas; Adan, Ivo (EAI Endorsed Transactions on Smart Cities, 2016)
This paper presents a preliminary assessment of the potential performance gains of a self-organized traffic light policy developed by Lämmer and Helbing. A large amount of data was obtained for a complex real-world intersection that serves as an ideal test-bed for comparison of traffic control policies. We provide evidence that a change in policy may drastically decrease average queue lengths and waiting times, suggesting the self organized policy is a promising approach to the control of traffic intersections deserving further investigation and potentially implementation.
Keywords: local control; dynamic control; traffic light policy; traffic network